FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN EKONOMI LOKAL (PEL) DI KOTA MEDAN (Studi Kasus Usaha Kecil Dan Menengah Sebagai Sektor Basis) - Sinaga, Anton Atno Parluhutan (UNIKA Santo Thomas, 2017)
The concept of Local Economic Development (LED) is an analytical tool that can be used to describe and measure economic conditions in a region. The territory in question may be administrative territory or region / region of particular business / commodity development, including small and medium enterprises (SMEs). Small and Medium Enterprises (SMEs) are part of the most strategic economic sector, concerning the livelihood of the people and is an important pillar in supporting and moving the joints of the economy in many countries .. SMEs play several important roles in Indonesia, one of them important players In Local Economic Development (LED) and community development. The purpose of this study is directed to determine the factors - factors that affect Local Economic Development with SMEs as the base sector in the city of Medan. The research method used in this research is Quantitative Descriptive Research Method. Data collection is done by using secondary and primary data. Then the analysis used to test the research hypothesis that has been determined by using the sample data obtained. The Inferential Statistics Method used in the analysis of this research data is Structural Equation Modeling (SEM). Descriptive result of this research is there are three variables have the average score of each - each variable is smaller than the middle threshold score 9. The three latent variables referred to include: social capital, socio-economic characteristics, and economic development policy However, when viewed From educational and skill perspectives, labor market and geographical characteristics greater than the middle threshold score 9. The results of this study are social capital, education and expertise, social characteristics, labor market, economic development policy and local culture are six factors Have a positive and significant impact on the succession of local economic development program of Medan city.